Fibrin-targeting immunotherapy protects against neuroinflammation and neurodegeneration. (November 2018) - Ryu, Jae; Rafalski, Victoria; Meyer-Franke, Anke; Adams, Ryan; Poda, Suresh; Rios Coronado, Pamela; Pedersen, Lars; Menon, Veena; Baeten, Kim; Sikorski, Shoana; Bedard, Catherine; Hanspers, Kristina; et al.
Abstract Activation of innate immunity and deposition of blood-derived fibrin in the central nervous system (CNS) occur in autoimmune and neurodegenerative diseases, including multiple sclerosis (MS) and Alzheimer's disease (AD). However, the mechanisms that link disruption of the blood–brain barrier (BBB) to neurodegeneration are poorly understood, and exploration of fibrin as a therapeutic target has been limited by its beneficial clotting functions. Here we report the generation of monoclonal antibody 5B8, targeted against the cryptic fibrin epitope γ377–395, to selectively inhibit fibrin-induced inflammation and oxidative stress without interfering with clotting. 5B8 suppressed fibrin-induced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase activation and the expression of proinflammatory genes. In animal models of MS and AD, 5B8 entered the CNS and bound to parenchymal fibrin, and its therapeutic administration reduced the activation of innate immunity and neurodegeneration. Thus, fibrin-targeting immunotherapy inhibited autoimmunity- and amyloid-driven neurotoxicity and might have clinical benefit without globally suppressing innate immunity or interfering with coagulation in diverse neurological diseases. Fibrin deposition occurs after the blood–brain barrier is breached. Akassoglou and colleagues generate a therapeutic monoclonal antibody that targets a cryptic fibrin epitope to suppress activation of innate immune responses in the CNS and diminish neuroinflammation.